Disparitas Putusan Mahkamah Konstitusi Terkait Sumber Daya Air; Studi Putusan Mahkamah Konstitusi Nomor 058-059-060-063/PUU/II/2004 dan Nomor 008/PUU-III/2005 dengan Putusan Mahkamah Konstitusi Nomor 85/PUU-XI/2013 - Maricha Nasution; JM Muslimin; Andi Syafrani (STAATSRECHT: Indonesian Constitutional Law Journal, 2019)
AbstractThis study discusses the results of a decision study on water resources in Indonesia. On the one hand the main focus of this study is the disparity in the decision of the Constitutional Court in deciding the same test, namely testing Law No. 7 of 2004 concerning Water Resources. On the other hand, this study also discusses the factors that cause disparities between the two Constitutional Court decisions related to water resources. Water is an important element in daily life and as a support for the needs of living things on earth. There is no water, then there is no life. Every year community growth continues to increase, so that the need for water also increases. Therefore, the regulation of water resources is needed. One of the good regulations on water resources is by prioritizing or prioritizing people's rights to water. The results of this study indicate that there are serious dilemmas and problems in the field of water resources, both from fulfilling water rights or water rights in Indonesia.Keywords: Disparity, Constitutional Court, Water Resources